Socio-demographic characteristics and ocular status of participants attending world glaucoma week screening - Abraham EG; Megbelayin EO; Ndubuisi C (Ibom Medical Journal, 2021)
Background: A large and growing body of evidence shows that socio-demographic factors – age, race, ethnicity and language as well as socioeconomic status (SES), such as income and education, can influence health seeking behaviours and thus health outcomes. Worldwide, the pattern of ocular diseases varies from one location to another. However, cataract, glaucoma, conjunctivitis, refractive errors, pterygium are considered the common ocular disorders. This study is aimed at finding the socio-demographic characteristics and ocular status of participants at a screening programme. Methods: A cross sectional population-based study conducted among individuals who voluntarily sought to be screened for glaucoma and ocular conditions during the 2020 World Glaucoma Week. Pre-validated self/interviewer administered questionnaire was used for socio-demographic information while clinical data was obtained from eye examination. Data so obtained was analyzed using SPSS version 25. Results: There were 139 (60.2%) female participants and 92 (39.8%) male participants in the ratio 1.5:1. Age group 31-40 years was the highest. Participants with post-secondary education only was 80 (34.6%) while 64 (27.7%) had primary education only, civil/public service was the highest occupation 72 (32.9%).The commonest diagnosis were presbyopia ±refractive error 56 (20.1%) and cataract 52 (18.6%). One hundred and sixty three (70.5%) had a VA of 6/18 or better while 39 (16.9%) had a VA of ≤3/60(CF) in the RE. Twenty one (10.4%) participants had a VCDR.>0.7 RE. Conclusion: Uncorrected refractive errors/ presbyopia remains the predominant cause of visual impairment. Cataract and glaucoma are still the commonest causes of preventable and avoidable blindness respectively.